Design and Implementation of IoT Energy Meter to Monitor Energy Flow at the Consumer End - Obulesu, Dakka; Phani Kumar, K. S. V.; V. Mahesh (Asian Journal of Electrical Sciences, 2019)
This paper presents a device that uses the evolving IoT technology to design and implement an internet-based energy meter. This meter, being cheap and easy-to-implement solution, enables consumers to monitor the daily usage of electric power easily. This work primarily concerns the energy-monitoring aspect of IoT, along with discussing other advantages of this meter, such as its ability to overcome human errors and reducing dependency on manual labor, besides reducing costs in energy consumption. The proposed design, which comprises a low-cost wireless network and protocol for smart energy along with a web application capable of automatically reading the unit and then sending the data automatically provides great advantages to users by allowing them to keep a track of their meter reading. This system will help users by allowing them to not only take steps to reduce power wastage but also bring down costs of consumption, along with minimizing the threat of power theft, which is incurs great losses to power companies. Experimental results of this study show that the proposed IoT meter works efficiently and has proven its potential in practical applications at substantially reduced costs.